A computer aided design system for product oriented manufacturing systems reconfiguration - Silva, Sílvio Carmo (2005)
Product Oriented Manufacturing Systems (POMS) are systems designed for variable product demand markets, and dynamically reconfigured for the manufacture of a single type of product or a family of similar products at a time. POMS systems can take several forms and result from exploring the use of flexible resources, a variety of new design philosophies, technologies and approaches to manufacture, including Cellular, Lean, Agile, Quick Response and Fit Manufacturing. In this paper a computer aided design system for the design and reconfiguration of POMS is addressed. A characterization and description of the structure and components of the design system, including a database, a user interface and a knowledge base and the description of some important data sets, are presented.